Computational exploration of Plant Ribosome Inactivating Proteins (RIPs) in countering Snake venom: A novel therapeutic opportunity and challenges - Uma , Palanikumar; Prasanna , Seenivasan; Thangavelu, AU; Bharathi , Nathan; Santhanakrishnan, Vichangal Pridiuldi; Renukadevi, Perumal; Rajagopal , Balasubramanian (Plant Science Today, 2025)
Snakebite envenoming represents a critical global health challenge, particularly prevalent in regions with limited access to healthcare resources, where venomous snakes pose a significant threat to human populations. Antivenom therapy which mainly rely on antibody production by immunization of large animals with venom components is labour intensive, time consuming and associated with various ethical concerns. Consequently, access to quality and affordable antivenom remains limited in many affected regions with high mortality associated with snakebites. In traditional medicine, many plant species have been ethnobotanically reported for their antivenom properties and are used to neutralize animal toxins. Ribosome-inactivating proteins (RIPs) are a diverse group of toxins found in various organisms, including plants that possess the ability to inhibit protein synthesis by irreversibly damaging the ribosomes. Even though considered to be harmful, the biological role of RIPs has gained increasing attention in recent years due to their potential therapeutic implications. With these insights, this review underscores the potential of RIPs as promising candidates for adjunct treatments in snakebite management strategies. In silico analysis by molecular docking of RIPs with major snake venom proteins resulted in effective binding and shows the interface residues involved in the interaction. This integrative approach enhances our understanding of snakebite pathophysiology, accelerating the development of novel next generation antivenom therapies that are safer and more effective.